Lipid nanoparticle-encapsulated, chemically modified anti-adenoviral siRNAs inhibit hepatic adenovirus infection in immunosuppressed Syrian hamsters - Anja Geisler; Babette Dieringer; Leslie Elsner; Karin Klingel; Robert Klopfleisch; Hans-Peter Vornlocher; Jens Kurreck; Henry Fechner (Elsevier, 2023)
RNA interference has demonstrated its potential as an antiviral therapy for treatment of human adenovirus (hAd) infections. The only existing viral vector-based system for delivery of anti-adenoviral artificial microRNAs available for in vivo use, however, has proven to be inefficient in therapeutic applications. In this study, we investigated the potential of stabilized small interfering RNA (siRNA) encapsulated in lipid nanoparticles (LNPs) for treatment of hepatic hAd serotype 5 (hAd5) infection in an hAd infection model using immunosuppressed Syrian hamsters. The siRNA sipTPmod directed against the adenoviral pre-terminal protein (pTP) and containing 2'-O-methyl modifications as well as phosphorothioate linkages effectively inhibited hAd5 infection in vitro. In light of this success, sipTPmod was encapsulated in LNPs containing the cationic lipid XL-10, which enables hepatocyte-specific siRNA transfer, and injected intravenously into hAd5-infected immunosuppressed Syrian hamsters. This resulted in a significant reduction of liver hAd5 titers, a trend toward reduced liver injury and inflammation, and reduction of viral titers in the blood and spleen compared with hAd5-infected animals that received a non-silencing siRNA. These effects were demonstrated in animals infected with low and moderate doses of hAd5. These data demonstrate that hepatic hAd5 infection can be successfully treated with anti-adenoviral sipTPmod encapsulated in LNPs.